Leading sector pertumbuhan ekonomi Provinsi Jambi - Rosmeli, Rosmeli (Program Studi Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Jambi, 2022)
The increase in economic development cannot be separated from the increase in the sectors that make up GRDP. The leading sector is a sector that plays an important role in the economy of a region. There are several approaches used to determine the leading sector in an area, including LQ (Location Quotient), MRP (Growth Ratio Model), Overlay and Shift Share Analysis. From the research results, it is known that based on LQ analysis, the leading sector in Jambi Province is still dominated by the primary sector. MRP analysis shows that all economic sectors in Jambi Province are not potential sectors based on growth criteria. From the overlay analysis, it is known that the agriculture, mining, water supply, government administration, education and health services sectors are sectors with low growth but have comparative advantages.